“All Politics is Local”: A Sociocognitive Investigation of Contexts as Indigenous Peculiarities in Gubernatorial Inaugurals - Adebayo Rasheed Mabayoje (Journal of Language and Literature, 2022)
Devised by Tip O'Neill, "all politics is local" relates to the standard that -as a politician- a new governor’s communicative skill is directly connected to the shared understanding of the peculiar situations of a particular locality, by which views regarding the governor’s new regime are presented in an inaugural speech (IS). This angle of contexts in IS pictures the cognitive bridge of language and society; and has received scarce scholarly attention, particularly from the sociocognitive perspective. They are, therefore, explored in this article along with peculiar activities and events (as issues) in the inaugural speeches of three Nigerian Governors- relying on insights from van Dijk’s Context Models and Fauconnier and Turner’s Conceptual Blending. Six discursive contexts –categorised under common (labour, restoration, electoral process), and distinctive (divine support, tradition and value, morality) -situated six issues in the speeches, in terms of how Governors Rauf Aregbesola (RA) and Olagunsoye Oyinlola exploited Osun people’s religious inclination; in terms of the disposition of RA’s regime to the ideals of some previous administrations; and in terms of how Adebisi Akande rationalised participants’ behaviours. The article argues that described events and ongoing discourses in a new governor’s IS are the subjective mental representations that typify participants’ indigenous peculiarities, and constrain communicative meaning derivations.